(untitled) (Journal of Economic Additions, 2025)
The study aims to identify the reality of the information and communication technology sector in Algeria in light of digital transformation, by using the descriptive approach in the theoretical aspect and the analytical approach in the applied aspect of the most important indicators of the postal and telecommunications sector.A case study of Algeria in the period (2017-2023). The study concluded that digital transformation contributes to the efficiency of the ICT infrastructure, increasing its ability to compete economically, and developing the digital economy.The study recommended the necessity of investing in the ICT infrastructure to meet technical challenges and improve competitiveness in the ICT sector in a way that supports digital transformation Jel Classification Codes: M15، L96، M19،C61